Digital adaptive governance and school safety: informatization for post-flood educational continuity in Aceh Barat Daya - Afdhal Jihad (Jurnal Mantik, 2026)
Recurrent flooding in Aceh Barat Daya severely disrupts school operations, threatens physical safety, interrupts learning access, and erodes community well?being. Existing research presents three key gaps: empirically, studies focus largely on infrastructure repair or traditional preparedness and rarely examine informatization as a governance capability; theoretically, models separate digital systems from adaptive leadership rather than integrating them; methodologically, accounts remain mostly descriptive without cross?case analysis of adoption processes. This qualitative multiple?case study investigates how three flood?prone public schools integrate digital systems, shared information platforms, and collaborative management to strengthen safety assurance, adaptive decision?making, and learning continuity. Data from interviews, documents, and observations were analysed using thematic analysis. Key findings identify four interconnected dimensions: digital early warning and coordination, data?driven governance, informatization?enabled hybrid continuity, and collective safety management. As a novelty, the study proposes the Digital Adaptive Educational Safety Framework, which unites these components while aligning technology with local cultural practices—shifting response from reactive to proactive. The findings advance understanding of how information systems build educational resilience, relevant for disaster?prone regions globally.